Representation of Dropsonde‐Observed Atmospheric River Conditions in Reanalyses. Issue 15 (9th August 2021) - Cobb, A.; Delle Monache, L.; Cannon, F.; Ralph, F. M.
Abstract: Atmospheric rivers (ARs) are the primary mechanism for mid‐latitude water vapor transport, and are identified by a key variable, integrated water vapor transport (IVT). The ability of atmospheric reanalyses in providing a ground‐truth dataset for the IVT field is assessed by comparing ERA5, MERRA‐2, and JRA‐55 data against a large sample (>1, 700) of dropsonde profiles deployed in and around ARs. Bias and error increase with IVT magnitude, although asymmetrically around the AR core. A partitioning of the source of error reveals that humidity contributes more to the difference in IVT above 800 hPa, while wind is the dominant source in the lowest levels (to 950 hPa). This quantification of reanalysis error and bias identifies ERA5 as the dataset with the lowest IVT errors and demonstrates remaining challenges in representing the observed state in ARs. Plain Language Summary: Atmospheric rivers (ARs) are long, narrow features in the atmosphere that transport significant amounts of water and energy from lower to higher latitudes, and are identified by integrated water vapor transport (IVT). In this study we compare IVT from >1, 700 dropsonde observations to atmospheric reanalyses, a gridded dataset of past atmospheric states constrained by observations. We identify ERA5, the most recent reanalysis with the highest spatial resolution, as the dataset with the lowest IVT errors. IVT is a product of wind and humidity, and we find that the reanalysis wind contributes more to the difference from dropsonde IVT in the lowest layers than reanalysis moisture. Key Points: Quantify reanalysis error and bias compared to dropsonde integrated vapor transport (IVT) ERA5 simulates integrated vapor transport (IVT) at these point locations better in terms of correlation and standardized error Reanalysis bias and error increase with integrated vapor transport (IVT) magnitude, although asymmetrically around the atmospheric river (AR) core